Structural studies of the capsular polysaccharides from some strains of Klebsiella and Cryptococcus neoformans micro-organisms - Merrifield, Edwin Howard (Department of Chemistry, 2023)
The structures of the exopolysaccharides from a number of strafos of the bacterial genus KlebsieUa have been investigated and compared. ·All of these polysaccharides have been shown to be composed of regularly repeated oligosaccharide units containing -glucuronic acid and three to five hexose residues, with pyruvic acid ketal and 0-acetyl groups also present in some of the polysaccharides. Graded acid hydrolysis, monitored by gel-permeation chromato graphy, has been used to study the degradation of each polysaccharide to the structurally significant oligosaccharides and fragments of higher molecular weight which are clearly aggregates of these units. In all cases both acidic and neutral oligosaccharides have been isolated in a high degree of purity, which has permitted their characterisation by standard techniques, including partial acid hydrolysis and methylation analysis, and the use of proton magnetic resonance spectroscopy and measurement of optical rotatory power to determine the nature of anomeric linkages. The polysaccharides from Klebsiella K4 and X.pnev.moniae ( oxytoca variant) have been shovm to have linear tetra- and pentasaccharide repeating units respectively, while the structures of those from serotypes K27 and K64 have been found to be more complex, consisting of branched hexasaccharide repeating units with pyruvic acid ketallinked to one sugar residue. In addition, the fungal polysaccharides from two strains of c1yptococcus neoformans have been investigated and shovm to be chemically equivalent. The evidence obtained from partial acid hydrolysis, methylation analysis and Smith-degradation studies performed on one of these polysaccharides is consistent with a structure in which a linear (l-+3)- linked chain of -mannose residues is substituted at position C-2 by either g-glucuronic acid or ll_-xylose. This represents one of the few complete characterisations of a Cryptococcus polysaccharide to be achieved up to the present.